(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Online teaching is increasingly common at many types ofhigher education institutions, ranging from hybrid courses that offer acombination of in-person and online instruction, to fully online experiencesand distance learning. The following resources provide guidelines for creatingan online course, best practices for teaching online, and strategies forassessing the quality of online education. Online faculty needto engage the student. Online course work is now an integral element ofmainstream. Online courses often lack face-to-face interaction, peerinteraction, faculty feedback and the lack of community. Engagement of thelearner is essential for learning and promoting student satisfaction. There areonline teaching strategies that could enhance a student’s perception ofengagement. With the growing awareness of the importance of teachingand learning in universities and the need to move towards evidence-basedteaching, it behooves the professions to re-examine their educational researchmethodology. While the what, how and why of student learning have become moreexplicit, the professions still struggle to find valid methods of evaluatingthe explosion of new innovation in teaching/learning strategies. This paperdiscusses the problems inherent in applying traditional experimental designtechniques to advances in educational practice.